2009
DOI: 10.1590/s0100-40422009000900013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the major nutritional components of Caryocar brasiliense fruit pulp by nmr spectroscopy

Abstract: Pequi (Caryocar brasiliense Camb.), a typical fruit of Brazilian Cerrado, is well known in regional cookery and used in folk medicine to treat various illnesses. Mass spectrometry and chromatographic methods have identified the organic composition of pequi fruit pulp; however, NMR spectroscopy is used for the first time to characterize the nutritional components of organic and aqueous-ethanolic extracts. This spectroscopic technique determined the triacylglycerols in the pequi organic fraction, which is consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 9 publications
(24 reference statements)
3
22
0
5
Order By: Relevance
“…There can be changes in blood values during and after intensive exercise caused by differences such as the state of individual training, environmental factors, and nutrition [14,35,41,71,135,139], and the only change in the athletes' routine between the two races was the supplementation with pequi oil. Moreover, previous results of our group which investigated the antioxidant effects of pequi oil on the same runners through measurements of creatine kinase (CK), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) [89] corroborate the suggestion above, since they did not exceed the reference values proposed for clinical purposes [46,67,120] and much less for athletes [96] in both before and after pequi-oil supplementation, besides reducing DNA damage after pequi. Additionally, in the immediate post-exercise period an increment of 50-100% of total leukocytes occurs, mainly due to neutrophilia and lymphopenia, as well as monocytosis, which also occurs at a lower rate [35], and results of leukogram and plateletgram were inside the reference values [67,137] after both races, independently of sex, age group, or distance covered.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There can be changes in blood values during and after intensive exercise caused by differences such as the state of individual training, environmental factors, and nutrition [14,35,41,71,135,139], and the only change in the athletes' routine between the two races was the supplementation with pequi oil. Moreover, previous results of our group which investigated the antioxidant effects of pequi oil on the same runners through measurements of creatine kinase (CK), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) [89] corroborate the suggestion above, since they did not exceed the reference values proposed for clinical purposes [46,67,120] and much less for athletes [96] in both before and after pequi-oil supplementation, besides reducing DNA damage after pequi. Additionally, in the immediate post-exercise period an increment of 50-100% of total leukocytes occurs, mainly due to neutrophilia and lymphopenia, as well as monocytosis, which also occurs at a lower rate [35], and results of leukogram and plateletgram were inside the reference values [67,137] after both races, independently of sex, age group, or distance covered.…”
Section: Discussionsupporting
confidence: 72%
“…), a typical fruit found in the Brazilian Cerrado, had anti-inflammatory properties, besides reducing arterial pressure, exercise-induced DNA, tissue damages, and anisocytosis [88,89,92]. Although the protective effects of pequi oil are unquestionable, some of these responses were influenced by genetic polymorphisms related to oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…trans-Phytyl palmitate (4) (Asand et al 1991), linoleic acid (5) (Gunstone 2007;Gunstone & Jacobsberg 1972), methyl oleate (6) (Gunstone 2007;Rakoff et al 1979), ethyl palmitate (7) (Gunstone 2007;Joshi et al 2009) and palmitate acid (8) (Gunstone 2007;Miranda-Vilela & Grisolia 2009) are common known fatty-acids or fattyesters. The structures of the compounds were established by comparing the experiment data with the reported data.…”
Section: Resultsmentioning
confidence: 99%
“…[29,30,44] Physical exercise involves the entire body in terms of energy metabolism, hormonal mobilization and action, signal transduction process, immunological responses and adaptations [43] and other reports with lower or equal intervention times have also shown physiological effects, with significant changes in the biochemical markers used. [45][46][47][48] Pequi oil contains several carotenoids, [24][25][26][27] recognized as an effective antioxidant under low PO 2 conditions [2] such those undergone by various tissues and organs during races. In addition, it has been reported that meals rich in monounsaturated fatty acids, as provided by the Mediterranean diet and by pequi-oil supplementation, increases plasma carotenoids, [46] which can improve antioxidant defense in situations of increased oxidative stress.…”
Section: Wwwantioxorg Discussionmentioning
confidence: 99%
“…The internal mesocarp was peeled to obtain pulp, extracted by cold maceration using chloroform as solvent, submitted to evaporation under reduced pressure for solvent removal and dried at high vacuum. Pequi oil, whose relative composition is shown in Table 1, [24][25][26][27] was then incorporated in Aerosil q.s.p., so that users ingested a daily dose of 400 mg. Capsule production was patented as PI0601631-6 (National Institute of Industrial Property -INPI).…”
Section: Preparation Of Capsulesmentioning
confidence: 99%